IMPLEMENTASI SISTEM TRANSAKSI NON TUNAI DALAM PELAKSANAAN BELANJA PEMERINTAH DAERAH UNTUK MEWUJUDKAN PRINSIP GOOD GOVERNANCE (Studi Kasus Pada Badan Kesatuan Bangsa Dan Politik Kabupaten Indragiri Hilir) - EMELDA EMELDA; SURYANI SURYANI; IRA GUSTINA; NOVRIANI SUSANTI (JURNAL AKUNTANSI DAN KEUANGAN, 2026)
The implementation of cashless transactions aims to improve accountability, transparency, and efficiency in the management of local government expenditures. However, an evaluation of its effectiveness in realizing the principles of good governance is still needed. This study analyzes cashless payment procedures and their role in realizing the principles of good governance at the Office of National Unity and Politics of Indragiri Hilir Regency. This qualitative descriptive study involved key informants, namely the expenditure treasurer, financial analysts, system operators, and budget users. Data collection was conducted through interviews, observations, and documentation, and was subsequently analyzed using interactive qualitative analysis. The results indicate that non-cash transactions have been implemented through structured payment procedures integrated with the banking system, thereby improving administrative order, accelerating payment processes, strengthening internal controls, and enhancing accountability and transparency. Although technical challenges exist, the implementation remains generally effective. Thus, non-cash transactions play a crucial role in supporting the realization of good governance principles in the management of local government expenditures.